Analiza porównawcza programów nauczania rachunkowości i oceny studentów w wybranych uczelniach polskich i zagranicznych - Niewiadoma, Maria (The Analysis of Concepts of Accounting Teaching and Students' Marking in Polish and Foreign Universities, 2005)
This article has been based on the Griffith University's materials from Australia (the Market and Management Faculty) and on the University of Economics in Wrocław connected with the academic principles of teaching accounting for students. Three subjects have been analysed on this specialization: Accounting Principles (or Accounting), Financial Accounting and Management Accounting and the forms of studies: lectures, seminars, laboratories, individual consultations with tutors and individual study materials from University's e-mail addresses). Last step, which has been analysed in this article - the possibility to estimate by the tutors the final points for student's index from the accounting subject: Tutorial Quizzes, Mid-semester exams, Group Assignment, Final Exam.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (3); 2005; nr 1062, s. 356-367